2023
DOI: 10.30935/cedtech/12987
|View full text |Cite
|
Sign up to set email alerts
|

Integrating cognitive presence strategies: A professional development training for K-12 teachers

Abstract: For K-12 teachers to improve effective teaching skills, cognitive presence (CP) integration into teaching and learning process is of utmost value. CP strategy training can serve as a facilitating component in supporting K-12 teachers’ instructional capacity. This study presents findings of a teacher professional development training aiming CP strategy implementation at K-12 level. Following a mixed-method methodology, the present research was carried out with 53 teachers from four different campuses and grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 69 publications
3
23
0
1
Order By: Relevance
“…Another finding from this study was that younger age groups agreed on the potential for benefits in higher education with the use of Generative AI. This supports previous research by Adiguzel et al (2023) who found that there is great potential for personalized learning, language instruction, and feedback applications in education by using Generative AI technology such as ChatGPT.…”
Section: Discussionsupporting
confidence: 90%
“…Another finding from this study was that younger age groups agreed on the potential for benefits in higher education with the use of Generative AI. This supports previous research by Adiguzel et al (2023) who found that there is great potential for personalized learning, language instruction, and feedback applications in education by using Generative AI technology such as ChatGPT.…”
Section: Discussionsupporting
confidence: 90%
“…Introducing ChatGPT: an AI language model that can revolutionize how learners engage with digital content (Adiguzel et al., 2023). When ChatGPT is utilized as a moderating tool inside the M‐learning environment, it can address the existing gaps in M‐learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Large language models (LLMs) are a type of AI trained to generate text similar to human‐generated text (Tate et al, 2022). LLMs have become increasingly popular in recent years and have been used for a variety of applications, including language translation, text summarization, and content generation (Adiguzel et al, 2023). These language models are called “large” because they are typically trained on a corpus of text data ranging from millions to billions of words (Brown et al, 2020).…”
Section: The Rise Of Generative Ai‐based Large Language Models Like C...mentioning
confidence: 99%